A Novel Insight Into the Fate of Cardiomyocytes in Ischemia-Reperfusion Injury: From Iron Metabolism to Ferroptosis - Li, Jing-yan; Liu, Shuang-qing; Yao, Ren-qi; Tian, Ying-ping; Yao, Yong-ming (Frontiers in Cell and Developmental Biology, 2021)
Ischemia reperfusion injury (IRI), critically involved in the pathology of reperfusion therapy for myocardial infarction, is closely related to oxidative stress, the inflammatory response, and disturbances in energy metabolism. Emerging evidences show that metabolic imbalances of iron participates in the pathophysiological process of cardiomyocyte IRI (also termed as myocardial ischemia-reperfusion injury (MIRI)). Iron is an essential mineral required for the vital physiological functions, including cellular respiration, lipid and oxygen metabolism, as well as protein synthesis. Nevertheless, cardiomyocyte homeostasis and viability are inclined to be jeopardized by iron-induced toxicity under pathological conditions, which is defined as ferroptosis. Upon the occurrence of IRI, excessive iron is transported into cellular that drives cardiomyocytes more vulnerable to ferroptosis by the accumulation of reactive oxygen species (ROS) depended on the mechanism underlying Fenton reaction and Haber-Weiss reaction. Elevated ROS production in ferroptosis correspondingly leads cardiomyocyte more sensitive to oxidative stress under the exposure of excess iron. Therefore, ferroptosis might play an important role in pathogenic progression of MIRI, and precise ferroptotic mechanisms are thought to be the promising therapeutic option to revert myocardial remodeling. Notably, targeting inhibitors are expected to prevent MIRI deterioration by suppressing the ferroptotic cell death of cardiac cells. Here, we review the pathophysiological alterations from iron homeostasis to ferroptosis together with potential pathway regarding to ferroptosis secondary to cardiovascular IRI. We also provide a comprehensive analysis of ferroptosis inhibitors and initiators, as well as regulatory genes involved in the setting of MIRI.